Arthroscopic-assisted percutaneous fixation of intra-articular calcaneal fractures using an intraoperative distraction device. (6th January 2021) - Gao, Di; Wong, Tak Man; Fang, Christian; Leung, Frankie KL; Li, Xiang; Jia, Bin; Wang, Yu; Yu, Bin
Purpose: To evaluate the quality of reduction and clinical outcomes by using Percutaneous Distractor and Subtalar Arthroscopy Closed Reduction followed by Internal Fixation (PDSA-CRIF) in the intra-articular calcaneal fracture. Methods: A consecutive case series of 453 patients with 507 displaced intra-articular calcaneal fractures was recruited in this retrospective study. We performed PDSA-CRIF to treat intra-articular calcaneal fractures. The quality of reduction was assessed by early postoperative Computed Tomography (CT) scans and measurement of serial Bohler's angles during follow-ups. Clinical outcomes were evaluated by Visual Analogue Scale (VAS) and the American Foot & Ankle Society ankle-hind foot scale (AOFAS) scoring system. Results: Fifty-nine patients (68 fractures) who had complete clinical data and follow-up of at least 12-months (mean: 14 months, range: 12–59 months) were finally included. Anatomical and near-anatomical reduction in subtalar articular surface which had less than 2 mm gap or step-off was found in 93% fractures. Unsatisfactory reduction was found in 7%. Conclusion: Arthroscopic-assisted percutaneous fixation using a distraction device is effective in achieving positive short-term results in the displaced intra-articular calcaneal fractures. A multicenter, large sample, randomized control trial is needed to fully evaluate the long-term effects of PDSA-CRIF in comparison to other methods.